2019
DOI: 10.24940/theijbm/2019/v7/i3/bm1903-004
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Labor Force Changes on Human Resource Management Activities in Vietnam

Abstract: Vietnam is facing the population aging trend, which has a direct impact on the aging labor force. That leads to change in human resource activities to create and sustain the human resource to meet the organization's goals. The question is that how the organization find appropriate ways to implement human resource management activities to adapt to the new situation. This research is about evaluating the impact of changes in labor force on human resource management in Vietnam based on statistical data and opinio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Clark et al (1999) and Lai and Yip (2022) found adverse relationship between labor force and economic development. On the other hand, Cung and Hung (2020) found that by boosting productivity, the work force boosts economic growth. Arguing similar, this study incorporates labor force to examine its impact on the economic growth.…”
Section: Macroeconomic Stability In Saarc Countriesmentioning
confidence: 99%
“…Clark et al (1999) and Lai and Yip (2022) found adverse relationship between labor force and economic development. On the other hand, Cung and Hung (2020) found that by boosting productivity, the work force boosts economic growth. Arguing similar, this study incorporates labor force to examine its impact on the economic growth.…”
Section: Macroeconomic Stability In Saarc Countriesmentioning
confidence: 99%